The CHAMPION trial outcomes were not adequately prespecified. - Dale, A; Drysdale, H; Heneghan, C (Elsevier, 2016)
The publication from William Abraham and colleagues (Jan 30, p 453) reports eight outcomes that were not appropriately prespecifi ed in the trial registry (NCT00531661) or in the Article reporting the study design.